Hyponatremia in Patients with Acute ST Elevation Myocardial Infarction: Evaluate the Short Term Outcomes - Mushtaq Ahmed Shahid, Shahzad Majeed Bhatti, Mahvesh Mahmud, Muddasar Pervaiz (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: Hyponatremia and its related short-term consequences such as death during hospitalization and heart failure in patients with acute myocardial infarction need to be studied. Study Design: Cross-sectional/observational study Place and Duration: Deptt of Cardiology, Fatima Jinnah medical university / Sir Ganga Ram Hospital Lahore. Dec 2020-Nov2021 Materials and Methods: A total of 125 patients, equally split across sexes, ranging in age from 18 to 80, were included in this research. After obtaining written agreement from patients, demographic data was collected. The sodium concentration in the blood was measured using blood samples taken from the participants. Sodium levels of less than 135 millimol/L (mmol/L) were characterized as hyponatremia. Death and heart failure were considered as outcomes. SPSS 22.0 was used to analyze the data. Results: Among 125 patients, there were 75 (60%) were male and 50 (40%) were females and had mean age 53.8±11.61 years. Frequency of hyponatremia was found among 52 (40%) patients and sodium level >135mmol/L was found among 73 (60%) patients.Among 52 hyponatremic patients, mortality was found among 27 (53.8%) and frequency of acute heart failure was found in 19 (36.5%) . Hyponatremia was shown to be associated with an increased risk of death in the hospital and acute heart failure, with a p-value of less than 0.05. Conclusion: According to the findings, hyponatremia is common in patients with acute mycocardial infarction and is related with a higher risk of death during hospitalization and an increased risk of acute heart failure.